CIVIC AGENCY DI ERA DEEPFAKE: STRATEGI PENDIDIKAN KEWARGANEGARAAN DALAM MENGHADAPI MANIPULASI INFORMASI VISUAL - Sasikirana Rizky Ramadhania; Nashera Rahman; Zaenul Slam (JISPE Journal of Islamic Primary Education, 2026)
The rapid development of artificial intelligence technology has given birth to the phenomenon of deepfakes, which are synthetic visual content that is able to convincingly manipulate a person's face, voice, and actions. This technology not only poses technical problems, but also threatens democracy, public trust, and the capacity of citizens to carry out their civic roles with dignity. This article aims to analyze the threat of deepfakes to civic agencies, identify the vulnerability of the digital generation to visual information manipulation, and formulate relevant and adaptive civic education strategies. The research method uses a systematic literature review of scientific publications in 2020–2025 with thematic analysis as an instrument for data interpretation. The results of the study show that the young generation is in a vulnerable position due to high exposure to digital content that is not balanced by adequate critical thinking skills. Civic education needs to transform through the integration of digital media literacy, visual information verification competencies, and strengthening digital ethics in the curriculum. This article offers a model of the Civic Agency Resilience Framework (CARF) that connects epistemic competence, democratic participation, and civic ethics, and encourages curriculum reorientation, teacher training, and cross-sector collaboration